Learning approaches of Indonesian EFL Gen Z students in a Flipped Learning context - Santosa, Made Hery (IAIN (State Islamic Institute) Palangka Raya, Indonesia, 2017)
The 21st-century learning has eventually transformed todayâs classroom. With more digital natives in the class, both educators and students face a changing classroom that should accommodate different learning paces, styles and needs. This study aimed at helping students in becoming English as Foreign Language (EFL) competent in-service teachers. Using Flipped Learning, the study utilizes four FLIP pillars into EFL learning, namely Flexible environment, Learning culture, Intentional content, Professional educators. The study employed three instruments, namely survey, tests, and interview. The result of tests showed a promising studentsâ progress from low to high achievement. The survey showed that students tended to perform deep approaches to learning while findings from the interview provided more interesting phenomena underlying studentsâ motives in their learning approaches, involving dynamic power distance relationship between lecturer and students. Heavier task loads and learning model familiarity have been highlighted. Effective socialization of the model using technology and sustainability of use of the model are suggested.